Poker w świetle ustawy o grach hazardowych i regulacji Unii Europejskiej - Lewandowicz, Maria; Kacprzak, Marek (Studia Prawa Publicznego, 2024)
The authors of the paper undertook an analysis of the regulations on the organization of a poker game under the Gambling Act. The main subject of the analysis revolves around the question to what extent state authorities should monitor and restrict the activity of poker players. The scope of the statutory restrictions on arranging and participating in poker games depends on the culture of perception of gambling in a given country. Assigning poker to the appropriate regulatory category, either as a gambling activity carrying the highest social risks in terms of public health or safety, or as a game primarily for entertainment, is by no means obvious and depends on determining such factors as the purpose of organizing the poker game and the manner in which it is played, i.e. whether players are playing against a casino or against each other. The regulatory differentiation depending on the variety of poker games is the result of years of efforts by national legislators and the jurisprudence to deﬁne and categorize the game correctly. The article cites the jurisprudence of the Constitutional Court justifying the formal and material prerequisites of the existing restrictions on the gambling services market. The authors also relied on the extensive body of case law of the Court of Justice of the European Union explicating the permissibility of restrictions on freedom of establishment and freedom to provide services in the sphere of gambling. The conclusions drawn from these reﬂections conﬁrm that the current provisions of the Polish Gambling Act are part of a consistent and systematic state policy aimed at ensuring the highest possible level of consumer protection, and the introduced restrictions are proportionate and necessary.